OCCURRENCE OF LISTERIA MONOCYTOGENES IN READY TO EAT FOOD SAMPLES COLLECTED BY LOMBARDY REGION HEALTH AUTHORITIES IN 2009-2010 - E. Oliverio; V. De Nadai; P. Daminelli; G. Finazzi; B. Bertasi; M.N. Losio (Italian Journal of Food Safety, 2012)
The study provides data on the prevalence of Listeria monocytogenes in ready-to-eat food samples collected by Lombardy region health authorities and analyzed by Department of Food Microbiology, Istituto Zooprofilattico Sperimentale della Lombardia e dell’Emilia Romagna. From the total of 503 food samples analyzed, the pathogen was detected in 85 (16,9%). In particular it was highlighted in 8/152 (5,3%) meat products, in 5/245 (2%) dairy products and in 42/106 (39,6%) fishery products. Given the considerable public health implications, the study confirms that a well-planned program of listeriosis surveillance should be enforced to suitably estimate the burden of disease and to prevent foodborne outbreaks.